The corrosion damage of an organic coating accelerated by different AC-DC-AC tests. (August 2021) - Xu, Yuqing; Song, Guang-Ling; Zheng, Dajiang; Feng, Zhenliang
Highlights: A more reasonale DC-AC-DC test was developed to accelerate the corrosion damage of organic coatings. The new method accelerates the damage without changing the degradation mechanism. The accelerated damage has the same morphology, composition and impedance behavior as natural immersion. Abstract: The corrosion damage of an organic coating system was accelerated by different AC-DC-AC tests in comprison with neutral salt spray (NSS) and natural immersionn. Electrochemical impedance spectroscopy (EIS), optical microscopy, scanning electron microscopy (SEM), laser microscopy, adhesion measurement, and energy dispersive spectroscopy (EDS) was employed to reveal the degradation processes of the coating. The results showed that the corrosion damage could be rationally accelerated in the same way as that in natural immersion condition if an alternate anodic polarization and a cathodic polarization were included in the DC step during the AC-DC-AC test. The accelerated corrosion damage had the same electrochemical behavior, surface morphology and product composition as that in natural immersion.